Congenital ranula: A case report - Rodrigues Cavalcante, Ana Sueli [UNESP]; Blumer Rosa, Luiz Eduardo [UNESP]; Sena Costa, Nívea Cristina [UNESP]; Hatakeyama, Márcia [UNESP]; Lia Anbinder, Ana [UNESP] (My University, 2009)
The purpose of this study was to report a case of bilateral swelling on the floor of the mouth of a 7-month-old patient. The lesion was congenital and had started to cause feeding problems. After the clinical diagnosis of ranula was made, the lesion was marsupialized. The obtained specimen was submitted for histopathological examination, which revealed an epithelial-lined cystic lesion. These results led to the final diagnosis of mucus retention cyst. After an 8-year follow-up period, the patient is in good general health with no recurrences.
Keywords: Children; Cyst retention; Marsupialization; Ranula; case report; human; infant; mouth; mucocele; pathology; Humans; Infant; Mouth Floor